Combination Intervention Mulligan’s Sustained Natural Apophyseal Glides and Ultrasounds Better Than Combination Intervention Stretching And Ultrasounds For Increasing Functional Activity Non-Specific Low Back Pain Patient - Putra, Yudi Pramana; Widnyana, M.; Saraswati, Ni Luh Putu Gita Karunia (Sport and Fitness Journal; Vol 10 No 1 (2022): Volume 10, No. 1, January 2022, 2022)
Abstract — Non-specific low back pain is one of the complaints that very often encountered with a picture of complaints originating without a clear cause. Non-specific low back pain is often a reason for the limitation of functional activity in patients because of pain symptoms and muscle tightness around the patient's lower back. The aim of this research is to prove that the Mulligan intervention, namely SNAGS as the latest intervention combined with physiotherapy modalities of ultrasounds, is more effective in improving the functional quality of non-specific low back pain patients than the combination of conventional stretching interventions with ultrasounds. The research method used in this study is the design of experimental research methods in the form of a pre-test and post-test two group design. In its implementation, there will be two groups with the number of each sample in each group consisting of 16 samples selected at random with the block permutation technique. Group 1 will receive conventional stretching and ultrasounds, while group 2 will receive mulligan's “sustained natural apophyseal glides” (SNAGS) and ultrasounds. The patient's functional activity was measured by the MODI (Modified Oswestry Disability Index) questionnaire. The study was conducted at a physiotherapy clinic in Denpasar. The results obtained in this study after processing the Paired T-Test test data in each group to determine whether there is a significant difference between pre and post from each combination, obtained with a p value <0.05, this indicates that there is a difference significant. The difference test between groups was carried out showing that there was a significant difference between the treatment group and the control group with the Independent T-Test test, getting a p value of <0.05 which has an interpretation of a significant difference. The conclusion obtained after the test and discussion of this study is that the mulligan intervention, namely SNAGS as the latest intervention combined with physiotherapy modalities of ultrasounds, is more effective in improving the functional quality of patients with non-specific low back pain than the combination of conventional stretching interventions with ultrasounds.   Keywords: Mulligan's SNAGS, Ultrasound, Conventional Stretching, Non Specific Low Back Pain, Decreased Functional Activity